The Effectiveness of Digital Marketing in Increasing Sales of MSME Products in Balikpapan - Indra Maulana; Dedy Rahmatullah; Nurfiza Widayati (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2026)
This study analyzes the effectiveness of digital marketing in improving the sales performance of Micro, Small, and Medium Enterprises (MSMEs) at the East Kalimantan MSME Gallery in Balikpapan. A mixed-method approach is employed, combining quantitative and qualitative analyses. The sample consists of 30 MSMEs, divided equally into 15 digital-based and 15 non-digital businesses, selected through purposive sampling. Quantitative data are analyzed using simple linear regression with Stata software, while qualitative insights are used to enrich the interpretation of the findings. The results indicate that digital marketing effectiveness has a positive and statistically significant impact on MSME sales performance, with a regression coefficient of 0.729 and an R² value of 0.8042, meaning that 80.42% of the variation in sales performance is explained by digital marketing effectiveness. Qualitative findings further reveal that MSMEs adopting digital platforms benefit from broader market access, increased customer reach, and stronger brand recognition. Overall, the study concludes that digital marketing plays a vital role in enhancing MSME competitiveness and supporting sustainable regional economic growth.